A complex heterozygous mutation in PADI6 causes early embryo arrest: A case report - Zhang, Ting; Liu, Peng; Yao, Guanfeng; Zhang, Xin; Cao, Cuijuan (Frontiers in Genetics, 2023)
Background: The PADI6 gene is a component of the subcortical maternal effect complex (SCMC). Mutations in the PADI6 gene, which was the first gene discovered to impact the activation process of the human embryonic genome, have been shown to induce early embryo arrest. Case: A 29-year-old lady with primary infertility underwent in vitro fertilization embryo transfer (IVF-ET) for tubal reasons, who had normal hormone levels and ovarian reserve. A Progestin-Primed Ovarian Stimulation (PPOS) protocol of Ovarian stimulation with IVF was performed. The total of Gonadotropin (Gn) stimulation with u-FSH was 2100 IU, which lasted for 10 days. When three follicles measuring less than 18 mm in diameter were seen, r-hCG 250ug and triptorelin acetate 0.2 mg were injected to trigger oocyte maturation. Nineteen oocytes (including thirteen MII oocytes) were picked up 37 hours after the trigger, and seven of these were normal fertilized. Unfortunately, these many embryos were stopped at the 1- or 2-cell stage, hence this infertile patient's IVF treatment won't result in an embryo transfer. Using whole-exome sequencing, a complex heterozygous mutation in PADI6 was discovered: c. 1247T>C [p.Ile416Thr] in exon 12 of PADI6, and c. 2009_2010del [p.Glu670GlyfsTer48] in exon 17 of PADI6. Conclusions: We found a complex heterozygous mutation in the PADI6 gene (c. 1247T>C; c. 2009_2010del) that caused embryos were arrested at the 1- or 2- cell stage. The discovery in this patient adds to the evidence showing the PADI6 gene mutation causes early embryo arrest in humans.